Prevalence and Risk Factors of Type 1 Diabetes Mellitus in Children: A Tertiary Care Experience - Shafaq, Faiqa; Sarwar, Benash; Fayyaz, Humaira; Gul, Sarooj (Indus Journal of Bioscience Research, 2025)
Background: Type 1 Diabetes Mellitus (T1DM) is emerging as public hot wicket mainly among children and the growth rate is highest in low and middle income countries like Pakistan. T1DM is characterized by autoimmune destruction of pancreatic beta cells and requires lifelong insulin therapy and close management. Data on its prevalence and risk factors associated with the infection in Pakistani children, however, are limited. Objective: The purpose of this study was to find out the prevalence and principal risk factors in T1DM among the children presenting to a tertiary hospital at Faisalabad, Pakistan. Methods: Cross sectional study was carried out using attached hospital Allied Hospital Faisalabad over a six months period (July–December 2024). A total of 384 1–18 years old children were screened. Structured questionnaires and chart reviews were used to collect data on demographics, clinical presentation and potential risk factors. Significant associations were identified by multivariate logistic regression analysis. Results: A total of 384 children was diagnosed, including 42 (10.9%) T1DM children. The female predominance (57.1%) and the mean age of 10.2 ± 3.6 years were observed. On the whole, most cases were from urban areas (73.8%), while the majority presented with a family history of the disease (64.3%). 38.1% were found to present with diabetic ketoacidosis. Family history of diabetes (OR: 3.76, p = 0.002), early exposure to cow’s milk (OR: 2.58, p = 0.031) and urban residence (OR: 2.94, p = 0.022) were the statistically significant risk factors for diabetes. Conclusion: This study reveals that T1DM is highly prevalent in children and early diagnosis and public health intervention are needed. Risk factors that can be modified include family history, urban living and early dietary exposures.